Spatial correlation function of intensity variations in the ground scintillation pattern produced by equatorial spread-F irregularities - Engavale, B.; Bhattacharyya, A. (My University, 2005)
A theoretical model is used to relate the spatial variations found in intensity scintillation patterns formed on the ground due to scattering of VHF radio waves by equatorial ionospheric irregularities, with the spatial structure of these irregularities. As equatorial ionospheric irregularities are closely aligned with the geomagnetic field, they may be considered to constitute a two-dimensional dispersive random medium. Electron density variations, which produce refractive index irregularities in the medium, are assumed to be characterized by a power law spectrum. A numerical solution of- the equation satisfied by the fourth moment of intensity variations, in the plane of the receiver, is obtained using the split step method. The S4-index, which is the standard deviation of normalized intensity variations as well as spatial correlation function of intensity, is obtained by considering special cases of the fourth moment of intensity variations. Variation of S4-index with the standard deviation of phase fluctuations imposed by the ionospheric irregularities is studied for irregularities with different power spectral indices. Effect of varying phase fluctuations on the 50% de-correlation scale length is also studied for weak as well as strong scintillations. The S4-index and spatial scale lengths in the ground scintillation pattern depend on parameters like thickness and height of the irregularity layer, background plasma density, standard deviation of electron density fluctuation and irregularity power spectrum. The theoretical model is used to understand the roles of these parameters in determining the S4-index and spatial correlation function of intensity in the ground scintillation pattern.
Keywords: Equatorial ionosphere; Ionospheric irregularities; Scintillations; Correlation function; Equatorial spread-F irregularities